Improving Students' Vocabulary Mastery Using Card and Board Games at the Fourth Year of SDN 1 Begalon in 2012/2013 Academic Year - Putri, Aldisie Etika, Drs. Djoko Srijono, M.Hum, Nur Hidayat S.Pd., M.Pd (2015)
The objectives of the research are 1) to describe the improving vocabulary mastery using card board games of the fourth grade students of SDN 1 Begalon, 2) to describe whether or not improving the vocabulary mastery of the fourth grade students of SDN 1 Begalon using card and board games is effective. The type of the research that is used by the researcher is action research. The subject of the research was the fourth year students of SD Negeri 1 Begalon Surakarta. Data of this research are the field note during the action, the interview script, lesson plan, and the score of pre-test and the post-test. The data sources are event, informants or respondents, and document. The researcher collected the data using qualitative and quantitative method. The quantitative data was collected from the students' vocabulary scores through test, while qualitative data was obtained from observations, interviews, and document analysis. The results of the research showed that from the implementation of card and board games at the fourth year of SDN 1 Begalon Surakarta, the vocabulary mastery of the students improve significantly. It can be seen from the achievement score of the students also improve and fulfilled the Minimum Requirement Score or in Indonesia it is called Kriteria Ketuntasan Minimum (KKM). From the test result, the mean score increased from cycle to cycle. The mean score of pre-test is 49.7, the mean score of post-test 1 in cycle 1 is 71.6, and the mean score of post-test 2 in cycle 2 is 76.8. The implementation of card and board games is effective to improve the students' vocabulary mastery and the conducive classroom situation.